Assessment of the Socio-Economic Consequences of Emergency Situations (On the Example of the Republic of Kazakhstan) - Narbayev, Kalizhan Anuarbekovich; Guseva, Valentina Ivanovna; Raimbekov, Kendebai Zhanabilovich; Kusainov, Arman Bulatovich (Economy of Regions, 2018)
Environmental problems concern both the economic and social interests of the Republic of Kazakhstan. Therefore, it is necessary to elaborate a common assessment methodology for socio-economic consequences of emergency situations. We suggested the original methodology for the evaluation of direct and indirect socio-economic consequences of emergency situations in the Republic of Kazakhstan. We have developed an algorithm for the evaluation of socio-economic consequences of emergency situations for Kazakhstan at the present stage. As a result of industrial and socio-economic development, a priority place in the system of national security belongs to a subsystem of ecological security. It is connected with the fact that ecology is indispensable for the survival of mankind in the conditions of the newest ecological shocks of the 21st century. Moreover, the ecological safety is a component for the sustainable development of the state economy as well as for its social prosperity. This circumstance is due to the fact that huge financial means will be spent on the liquidation of possible environmental disasters that may negatively influence further development of a state. Moreover, territories suffered from environmental disasters would be announced as the zones of disasters, where any socio-economic activity would be forbidden. There are many such examples in the history of Kazakhstan. We remember Semipalatinsk Nuclear. From 1949 until 1989, there were more than 450 explosions, during which more than 600 nuclear and thermonuclear devices were blown up. We would also like to note the region of the Aral Sea, where millions of hectares of the earth have been brought out of agricultural turn, as the mistake using the irrigation areas. These facts indicate that those enormous territories of the Republic became the zones of ecological catastrophe and cannot be used for the socio-economic activity.